2000
DOI: 10.1002/(sici)1097-4547(20000315)59:6<806::aid-jnr13>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in operant behavior and alteration of CA1, CA3 hippocampal dendritic arborization due to subicular lesions

Abstract: The deficits in operant behavior and the alterations in dendritic arborizations of Cornu Ammonis 1 and Cornu Ammonis 3 (CA1 and CA3) hippocampal areas were investigated in subicular lesioned rats. The subjects were female Wistar rats aged 120 days, and were divided into four groups: one serving as age-matched untrained control, a second group received training and sham lesioning, a third group were only trained, and the fourth group were first trained and then subjected to subicular lesions. The rats were food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Many studies have since shown that deprived conditions (Globus & Scheibel, 1967), deafferentation (Deitch & Rubel, 1984;Flores et al, 2005;Nutan & Meti, 1998;Works, Wilson, & Wellman, 2004), some clinical pathologies, and immune dysfunction (Grossman et al, 2003;Sakic et al, 1998) reduce dendritic arbors. In contrast, extensive training (Chang & Greenough, 1982;Nutan & Meti, 2000;Schallert, Kozlowski, Humm, & Cooke, 1997) or environmental enrichment (Camel, Withers, & Greenough, 1986;Faherty, Kerley, & Smeyne, 2003;Greenough & Volkmar, 1973;Kolb et al, 1998;Volkmar & Greenough, 1972) increase dendritic complexity. Additional studies have empirically confirmed that animals raised in enriched environments have measurable changes in the brain and show improved learning in a variety of mazes (see Rosenzweig & Bennett, 1996).…”
Section: Functional Significance Of Dendritic Complexity In Other Modelsmentioning
confidence: 99%
“…Many studies have since shown that deprived conditions (Globus & Scheibel, 1967), deafferentation (Deitch & Rubel, 1984;Flores et al, 2005;Nutan & Meti, 1998;Works, Wilson, & Wellman, 2004), some clinical pathologies, and immune dysfunction (Grossman et al, 2003;Sakic et al, 1998) reduce dendritic arbors. In contrast, extensive training (Chang & Greenough, 1982;Nutan & Meti, 2000;Schallert, Kozlowski, Humm, & Cooke, 1997) or environmental enrichment (Camel, Withers, & Greenough, 1986;Faherty, Kerley, & Smeyne, 2003;Greenough & Volkmar, 1973;Kolb et al, 1998;Volkmar & Greenough, 1972) increase dendritic complexity. Additional studies have empirically confirmed that animals raised in enriched environments have measurable changes in the brain and show improved learning in a variety of mazes (see Rosenzweig & Bennett, 1996).…”
Section: Functional Significance Of Dendritic Complexity In Other Modelsmentioning
confidence: 99%